An Exploratory Analysis of the Characteristics of Ideologically Motivated Cyberattacks. Issue 7 (3rd October 2022) - Holt, Thomas J.; Lee, Jin Ree; Freilich, Joshua D.; Chermak, Steven M.; Bauer, Johannes M.; Shillair, Ruth; Ross, Arun
ABSTRACT: Web defacement is a form of hacking that involves altering the content of a website, resulting in repairs to the website code, loss of revenue, internal loss of productivity, and reputational damage. Limited research has examined the frequency of web defacements, the factors that distinguish them from other hacking motives, and the extent to which the correlates mirror research on physical acts of ideologically-motivated crime. The current study examined over 2.4 million web defacements hosted in the U.S. from 2012 to 2016 to assess aspects of routine activities theory associated with target selection and attack methods among ideologically-motivated defacements. A binary logistic regression analysis revealed that ideologically-motivated defacers were more likely to use unknown vulnerabilities; engage in repeated attacks; target top-level domains linked to foreign nations; domains ending in.edu; and homepages within websites. The findings of this study suggest that the target selection process of ideologically-motivated defacers are more purposive and designed to draw attention to their cause, resembling target preferences of individuals who engage in physical violence in support of an ideological agenda.